Examining the Role for Donor-specific Antibody Testing in Simultaneous Liver-kidney Transplantation: A Single-center Analysis of Outcomes. Issue 5 (22nd April 2023) - Das, Anushka; Rocque, Brittany; Remulla, Daphne; Raza, Muhammad; Barbetta, Arianna; Bangerth, Sarah; Goldbeck, Cameron; Maw, Thin Thin; Kim, Jim; Kwon, Yong; Emamaullee, Juliet
Abstract : Background: Simultaneous liver-kidney transplantation (SLKT) is increasingly used for patients with concurrent end-stage liver and renal disease. Emerging evidence suggests that simultaneous liver transplant can provide a tolerogenic benefit to multiorgan transplant recipients. Posttransplant donor-specific antibody (DSA) may be associated with worse outcomes; however, the role for testing DSA in SLKT is unclear. Methods: This study retrospectively assessed the impact of DSA on outcomes following primary SLKT at a large-volume center between 2008 and 2018. Patients were grouped by positive DSA, negative DSA, and DSA not tested, and data were obtained from our institutional database and chart review. Results: The cohort included 138 SLKT recipients with a mean age of 56.1 ± 9.7 y; 61.6% were male, and 55.8% were Hispanic. Overall, 62 patients were tested for DSA posttransplant, and 33 patients (23.9%) had at least 1 DSA detected. A total of 34 patients (24.6%) experienced at least 1 episode of liver rejection, and 23 patients (16.7%) experienced kidney rejection. Over 50% of patients with de novo DSA changed status during their posttransplant course. Rates of both liver and kidney rejection were slightly higher in the DSA + group, but liver allograft, kidney allograft, and patient survival did not differ when grouped by whether DSA testing was performed or DSA positivity. Conclusions: These data demonstrate that SLKT is associated with excellent long-term patient and allograft survival with a relatively low rate of rejection. In our experience, testing for DSA does not impact SLKT outcomes‚ and further multicenter analyses are needed to establish standard of care. Abstract :